2020
DOI: 10.1038/s41467-020-19599-8
|View full text |Cite
|
Sign up to set email alerts
|

Multilayer stabilization for fabricating high-loading single-atom catalysts

Abstract: Metal single-atom catalysts (M-SACs) have emerged as an attractive concept for promoting heterogeneous reactions, but the synthesis of high-loading M-SACs remains a challenge. Here, we report a multilayer stabilization strategy for constructing M-SACs in nitrogen-, sulfur- and fluorine-co-doped graphitized carbons (M = Fe, Co, Ru, Ir and Pt). Metal precursors are embedded into perfluorotetradecanoic acid multilayers and are further coated with polypyrrole prior to pyrolysis. Aggregation of the metals is thus e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
164
1
1

Year Published

2021
2021
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 251 publications
(167 citation statements)
references
References 64 publications
1
164
1
1
Order By: Relevance
“…Thus, these catalysts should encompass the efficient active sites to optimize oxygen species adsorption for low overpotential, desirable pore organization to enhance active sites exposure and mass transport, as well as a predictable structure to unveil the ORR mechanism. [5][6][7] Due to maximized atom efficiency, single atom catalysts (SACs) have been regarded as promising substitute for Ptbased catalysts in heterogeneous ORR catalysis. [8] Over the last few years, the graduated escalation in catalytic activity of SACs has been attained, with single-atom Fe-N 4 site presenting the best one among vast metal-nitrogen (M-N x ) sites.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, these catalysts should encompass the efficient active sites to optimize oxygen species adsorption for low overpotential, desirable pore organization to enhance active sites exposure and mass transport, as well as a predictable structure to unveil the ORR mechanism. [5][6][7] Due to maximized atom efficiency, single atom catalysts (SACs) have been regarded as promising substitute for Ptbased catalysts in heterogeneous ORR catalysis. [8] Over the last few years, the graduated escalation in catalytic activity of SACs has been attained, with single-atom Fe-N 4 site presenting the best one among vast metal-nitrogen (M-N x ) sites.…”
Section: Introductionmentioning
confidence: 99%
“…Reproduced with permission. [133] Copyright 2020, Nature Publishing Group. configurations and local microenvironments, these heterogenized molecular SACs can serve as excellent model systems to reveal the structure-activity relationship in CO 2 RR.…”
Section: Heterogenized Molecular Sacsmentioning
confidence: 99%
“…d) Illustration of the preparation of Fe-SA-NSFC. Reproduced with permission [133]. Copyright 2020, Nature Publishing Group.…”
mentioning
confidence: 99%
“…Linking the FTIR results (Figure S7, Supporting Information) with the SEM observations The chemical state and elemental composition were quantitatively investigated by X-ray photoelectron spectroscopy (XPS). The high-resolution C 1s spectrum of N-NPC samples presented the peaks at 284.6, 285.7, 286.9, and 289.2 eV, which can be assigned to CC, CN, CO, and CO bonds, [29,30] respectively (Figure S9, Supporting Information). The high-resolution N 1s spectrum revealed that the N dopants can be divided into pyridinic N (398.7 eV), graphitic N (400.9 eV), and oxidized N (403.0 eV) (Figure 2c).…”
Section: (3 Of 7)mentioning
confidence: 99%